SENTENCE BUILDING MASTERY: A STUDY OF STUDENTS' WRITING SKILLS - Muchsin Muchsin (JURNAL EDUKASI EL-IBTIDA'I SOPHIA, 2024)
This research focuses on evaluating the writing skills of students majoring in English at Muhammadiyah University of Tangerang. It examines five key aspects of writing: content, organisation, grammar, vocabulary and mechanics. The main aim is to assess students' English proficiency, especially in recount text, based on these indicators, while identifying common challenges they face in the writing process. Using quantitative research methodology, this study involved participants who were in their third semester. Data was collected through writing tests administered to the students and analysed using Heaton's Writing Assessment Criteria. The results showed that 52% of the students scored excellent to very good in terms of content, while 57% scored similarly in terms of organisation. In addition, 70% of students scored excellent to very good in grammatical accuracy and 70% scored excellent to very good in vocabulary use. In terms of mechanics, 63% were also in the good to very good range. Despite these positive results, the study identified several problems that students face in their writing efforts. Firstly, there are challenges in developing ideas effectively. Secondly, although students demonstrated an adequate understanding of their topic, some students struggled to articulate their insights. Finally, the results of the analysis show that students do not have significant difficulties in using past tense structures.